The Distinction of Personal Factors on Perception of Environmental Problems: Thai adolescence - Chanon Tunprawat; Yanin Rugwongwan; Wichitra Singhirunnusorn (My University, 2017)
This research was to study the environmental perception of the difference of personal factors. Sixteen environmental problem issues were used to study. The research instrument used in this study was the measurement of perceiving levels using Likert scale 1-5 questionnaires. The samples were 120 undergraduate students in Rajamangala University of Technology Phra Nakhon, Bangkok, Thailand. The sampling was nonprobability sampling, the statistical analysis was T-test and analysis of variance (ANOVA). The research finding found that the distinction between personal factors affects the level impact of perception of environmental problems issues on statically significant.
Keywords: Statistical Analysis; Research method; Environmental Education and Sustainability